Lukyanova T. H. Genre and stylistic features of subtitle translation (based on English feature films) - Lukyanova T. H. (Philological Treatises, 2020)
Our research is dedicated to issues of faithful subtitle translation of feature films from English into Ukrainian, genre and stylistic features in particular. The article deals with the theoretical aspects of feature film translation, defines such terms as film text, film translation, subtitling, compares translations of such linguistic elements as realia, colloquial vocabulary, slang, studies translation of metaphors, metonymy and euphemism.